ok, when we are dividing fractions, what we do is that we take the inverse of the fraction on the bottom (meaning i just flip it upside down) and multiply it by the top, and that's our solution

e.g. (2/3) / (4/5) = (2/3) * (5/4) = 5/6

when dividing by whole numbers, its the same principle. think of any whole number as itself over 1. so think of 5 as 5/1, or 9 as 9/1, so

e.g. (2/3) / 9 = (2/3) / (9/1) = (2/3) * (1/9) = 2/27

now to your problem. the first thing we have to do is change 4 3/5 to an improper fraction (i hope you know how to do that), the result is 23/5

so now, (23/5) / 5 = (23/5) / (5/1) = (23/5)*(1/5) = 23/25